2013
DOI: 10.1364/josaa.30.000791
|View full text |Cite
|
Sign up to set email alerts
|

Photon diffusion in a homogeneous medium bounded externally or internally by an infinitely long circular cylindrical applicator V Steady-state fluorescence

Abstract: As Part V in our series, this paper examines steady-state fluorescence photon diffusion in a homogenous medium that contains a homogenous distribution of fluorophores, and is enclosed by a "concave" circular cylindrical applicator or is enclosing a "convex" circular cylindrical applicator, both geometries being infinite in the longitudinal dimension. The aim is to predict by analytics and examine with the finite-element method the changing characteristics of the fluorescence-wavelength photon-fluence rate and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 30 publications
(79 reference statements)
0
2
1
Order By: Relevance
“…This result is similar to what would be expected from an analytical process to solve for diffuse fluorescence with two coupled diffusion processes giving the bi-phasic outcome. 38 The scattering coefficients that we have determined here differ from the values found in other studies, except the value at the concentration of 1% as discussed earlier. There are limited studies, which do not always overlap (see Hohmann et al 39 for an example), and did not return the experimental behaviour we have observed.…”
Section: Resultscontrasting
confidence: 82%
“…This result is similar to what would be expected from an analytical process to solve for diffuse fluorescence with two coupled diffusion processes giving the bi-phasic outcome. 38 The scattering coefficients that we have determined here differ from the values found in other studies, except the value at the concentration of 1% as discussed earlier. There are limited studies, which do not always overlap (see Hohmann et al 39 for an example), and did not return the experimental behaviour we have observed.…”
Section: Resultscontrasting
confidence: 82%
“…The unified analytical treatment of photon diffusion in both "concave" and "convex" geometries, in comparison to "semi-infinite" geometry to which the "concave" and "convex" geometries approach as the radius becomes infinite, has been demonstrated for continuous-wave (CW) [25], frequency-domain (FD) [26], and CW fluorescence [27] measurements. This particular study extends the analytical methodology introduced in [25][26][27] to modeling time-domain (TD) photon diffusion in the specific "concave" and "convex" geometries. The objective is to examine the effect of the "concave" or "convex" shape of the medium-applicator interface and the dimension (radius) of the interface on TD photon diffusion.…”
Section: Introductionmentioning
confidence: 99%
“…The spatial dependence of the sensitivity of FDOT is also specific to the applicator-medium geometry. Among the applicator-medium geometries that have been investigated for the potential of clinical application of FDOT, an axial outward-imaging geometry [16,17] for endo-rectal or endoscopic imaging is subjected to arguably much stronger variation of the sensitivity of surface measurement with respect to the imaging depth [18], when compared with the geometries involving a curved interface that encloses the medium [12] or a planar interface [15]. For example, the spatial sensitivity of a circular array with optodes evenly distributed along the circumference [11][12][13] is nearly azimuthally uniform; and the spatial sensitivity of a near-planar array with orderly distributed surface optodes or remote source-detector positions [14] changes insignificantly over the lateral dimension of the array.…”
Section: Introductionmentioning
confidence: 99%